Internalisasi Islam Nusantara pada Gending Jawa Campursari dalam Haul Sunan Ngeseng Gesing Semanding Tuban - Muhamad Fatkul Majid; Bagus Indrawan; Ahmad Khotibul Umam; Nurul Hakim (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to examine in depth how the values of Islam Nusantara are internalized through Javanese campursari music in the Haul tradition of Sunan Ngeseng in Gesing, Semanding, Tuban. This study is considered relevant because the haul tradition is understood not merely as a religious ritual practice but also as a cultural space that integrates religious and cultural dimensions into community life. In this context, Javanese campursari music serves not only as entertainment but also as a medium for conveying Islamic messages that reflect the process of acculturation between Islamic teachings and local wisdom. This research employs a qualitative approach with a descriptive design to obtain a comprehensive understanding of the phenomenon under study. Data were collected through direct observation of the haul implementation, interviews with community leaders and campursari performers, and supported by documentation and a relevant literature review. Furthermore, the data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that Javanese campursari music in the Haul tradition of Sunan Ngeseng plays a significant role as a medium for internalizing the values of Islam Nusantara. Values such as monotheism (tawhid), moral formation, and respect for religious scholars are conveyed through lyrics, musical elements, and cultural symbols that are closely tied to the community's daily life. The integration of performing arts and religious rituals reflects the characteristics of Islam Nusantara, which are inclusive, adaptive, and harmonious with local culture. Therefore, this study highlights the importance of preserving cultural traditions as a medium of cultural da'wah and encourages further academic exploration on the relationship between art, culture, and religion in society.   Keywords: Islam Nusantara, Campursari, Haul Of Sunan Ngeseng, Local Culture, Cultural Da'wah